Nitromethane ignition behind reflected shock waves: Experimental and numerical study. (15th October 2016) - Mathieu, O.; Giri, B.; Agard, A.R.; Adams, T.N.; Mertens, J.D.; Petersen, E.L.
Abstract: Ignition delay times for nitromethane have been measured behind reflected shock waves over wide ranges of temperature (875–1595 K); pressure (2.0–35 atm); equivalence ratio (0.5, 1.0, and 2.0); and dilution (99, 98, 95, and 90% Ar by volume) using a L9 Taguchi array. Emission from excited-state hydroxyl radials (OH ∗ ) was the primary diagnostic for determining the ignition delay times from the experiments. Results showed that nitromethane's ignition delay time is very sensitive to most of the experimental parameters that were varied. In addition, the OH ∗ profile for nitromethane presents an interesting double feature, with the relative intensity between the two peaks varying greatly depending on the experimental conditions. A detailed chemical kinetics mechanism was assembled from previous work by the authors and from sub-mechanisms from the literature. The latest theoretical work on nitromethane decomposition was used, and the final mechanism satisfactorily reproduces the ignition delay time data from the present study, as well as nitromethane and CH4 /NOx ignition delay time data available from the literature.